1990
DOI: 10.1111/j.1398-9995.1990.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketanserin, a new blocking agent of the 5‐HT2 receptor, on airway responsiveness in asthma

Abstract: Most of the antihypertensive drugs have a liability for adverse effects in asthma. Since there are few available data on the effect of ketanserin, a new antihypertensive drug which is a type-2 serotonin receptor antagonist, on human respiratory function, we have tested whether this drug can modify bronchial hyperresponsiveness to methacholine in asthmatic patients. The protective effect of intravenous ketanserin (0.14 mg/kg) was small, but significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Since ketanserin competitively antagonized the 5-HT-induced contraction with a pK B value 9.15 in accordance with 9.4 in mouse aorta [25], we could demonstrate that the contraction was mediated via 5-HT 2A receptors. In analogy with a contractile role for 5-HT 2A receptors in the airway, ketanserin, has been demonstrated to decrease ovalbumin-induced airway hyperresponsiveness in mouse [26] and to be beneficial in asthmatic subjects [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Since ketanserin competitively antagonized the 5-HT-induced contraction with a pK B value 9.15 in accordance with 9.4 in mouse aorta [25], we could demonstrate that the contraction was mediated via 5-HT 2A receptors. In analogy with a contractile role for 5-HT 2A receptors in the airway, ketanserin, has been demonstrated to decrease ovalbumin-induced airway hyperresponsiveness in mouse [26] and to be beneficial in asthmatic subjects [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which the effects of 5-HT were mediated is difficult to interpret in these studies as ketanserin, the 5-HT2 antagonist used in the study, also antagonizes the CCR3 receptor. Additionally, another study investigating bronchospasm in asthmatic humans showed that ketanserin had a protective effect on adenosine-induced bronchoconstriction (21). However, the mechanism by which ketanserin elicited these protective effects was not determined.…”
Section: Discussionmentioning
confidence: 99%
“…Doses used were adapted from other studies in which mice were treated with these receptor antagonists (Oishi et al , 1993; Garssen et al , 1993; Shaoheng & Walls, 1997) or according to the manufacturer's advice. Furthermore, animals were injected with a combination of cimetidine (10 mg kg −1 ) and ketanserin (12 mg kg −1 ) or with an α‐adrenoceptor antagonist (phentolamine, 5 mg kg −1 ) since ketanserin also has effects on these receptors (Cazzola et al , 1990). Control mice were injected with 0.25 ml sterile saline.…”
Section: Methodsmentioning
confidence: 99%